Plasmapause surface wave oscillates the magnetosphere and diffuse aurora - Fei He (Nature Portfolio, 2020)
Theoretical studies suggested that plasmapause surface waves related to the sharp inhomogeneity exist and act as a source of geomagnetic pulsations. Here, the authors show direct observations of a plasmapause surface wave and its impacts during a geomagnetic storm using multi-satellite and ground-based observations.